Cosmopolitism revisited: reading "Arredor de si" as an intervention - Allegue Leira, Alberto; Fernández Pérez-Sanjulián, Carme (Madrygal. Revista de Estudios Gallegos, 2014)
Arredor de si (1930), one of the most relevant novels in 20th century Galician literature, has been widely seen as a cronicle of the intelectual standing achieved by the group Nós to which its author, Ramón Otero Pedrayo, belonged. In this review a new perspective is noted by relating a central subject in the book, cosmopolitanism, to the debate promoted by a new generation of young writers on the pages of journal El Pueblo Gallego. They would publicise their direct knowledge of Europe in order to question the project till then developed by Galician nationalists. Arredor de si should be read as an intervention in that debate.
Keywords: Galician Literature; Arredor de si; Ramón Otero Pedrayo; El Pueblo Gallego; Nueva Generación Gallega; Galician Nationalism.